Analisis Pemahaman Konsep Dasar Perkalian Bilangan Cacah Siswa Kelas III Sekolah Dasar - Nurhasni Nurhasni; Syahfutra, Bayu Rahman; Chandra Chandra (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
Understanding the basic concept of multiplication is one of the important competencies that must be possessed by elementary school students. This study aims to analyze the extent of understanding the concept of multiplication of whole numbers in third grade elementary school students. A strong understanding of the concept at the initial stage is very important as a basis for mastering subsequent materials. This study uses a qualitative descriptive approach with data collection techniques in the form of diagnostic tests. The test is designed to identify the level of understanding of third grade elementary school students. The subjects of this study were third grade elementary school students. The results of the mini-research showed that some students had difficulty understanding story problems so that they considered them to be additions, errors when reading multiplication problems, and misconceptions that emerged in solving multiplication problems. Students had great difficulty making mathematical forms from story problems. These findings provide an important picture for teachers to design more effective learning and adjust their learning needs. Keywords: understanding concepts, mathematics learning, multiplication.